LITHUANIAN CONSUMERS’ VIEWS ON COUNTRY OF ORIGIN LABELLING FOR MILK AND DAIRY PRODUCTS - Ovidija EIČAITĖ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aimed to investigate Lithuanian consumers’ views on country of origin labelling for milk and dairy products. In order to get necessary information, Lithuanian residents were interviewed. A multi-stage stratified random sampling was used to select the respondents. A survey of 1,000 Lithuanian consumers on milk and dairy products was undertaken. The analysis of collected data was performed using the methods of mathematical statistics. The survey results reveal that for two-third of Lithuanian consumers, when buying milk and dairy products, it is important to know the country where the milk is milked. Respondents who perceive origin labelling indicating the country of milking as very important and important information tend to be female, middle-aged and have a higher education. While Lithuanian consumers are interested in origin labelling indicating the country where the milk is milked, they are not ready to buy milk and dairy products at a higher cost to have that additional information. Only one-third of interviewed persons are prepared to pay a price premium to know the country of milking. Respondents who are prepared to pay a little more to have that additional information tend to be young, have a higher education and the highest income.